The Role of Mass Media in Indonesian General Elections - Fikri Fikri Arrahman; Geardena Putra; Helmy Prima (Cakra Communico: Journal of Communication Science, 2024)
General elections are a very fundamental democratic process in building and maintenance balanced and stable political activities. The mass media has a strategic role in monitoring and supervising every stage of the elections, US well US building public trust in the election process. The mass media carry out reality construction on events that have been accepted as sources of information to form public opinion in accordance with the media narrative. This journal uses a qualitative descriptive approach with primary and secondary data analysis. This research method adopts the Miles and Huberman Theoretical Framework for the process of collect and analyzing data simultaneously. This qualitative method is comprehensive and detailed in outline and aiming to reveal the uniqueness of individuals, groups, communities and/or organizations in everyday life with scientific accountability. Then analyze the data by applying a reality construction according to Berger and Luckmann. This journal found that mass media has a significant effect on public trust in the election process and builds honesty and transparency in the election process. Therefore, it is important to improve the quality of election administration and improve the function of election supervision, US well US increasing the independence of the mass media so that they provide correct and honest information to the public.